A inclusão do indivíduo surdo no âmbito empresarial: a (não) atuação do intérprete de Libras nesse contexto - Ponpeo, Amanda Beatriz (Universidade Federal de São Carlos, 2021)
The present work aims to analyze how the inclusion of deaf professionals in the business environment, and the insertion of these professionals is predominantly through of Law nº 8.213/91, known as the quota law. Bibliographic research carried out indicate that the linguistic difference that the deaf have compromises their accessibility in places where the predominant language is the oral language. Thus, throughout this research, some challenges that can be faced by the deaf in these spaces of work (from being hired, to activities performed in daily work), in addition to highlighting the importance of the sign language translator and interpreter in this context. For this, we interviewed, through questionnaires, a Human Resources professional of a company (responsible also for hiring deaf professionals) and a social worker who works in an institution that serves the deaf, making the capture of curricula, referrals of these professionals to the market and training of contractors. Our analyzes indicate that there is a "preference" on the part of the contracting parties in relation to the oralized deaf people, showing the little importance given to the Libras interpreter in the context and, consequently, to the needs and rights of the deaf. We question, with our results, the ways in which deaf people have been “included” in the labor market, discussing the need to consider the full fulfillment of rights so that a truly inclusive work environment for the deaf.
The inclusion of the deaf individual in the business scope: a (no) performance of the Libras interpreter in this context
Keywords: Mercado de trabalho; Surdez; Inclusão; Tradução e interpretação em Libras; Funcionários surdos; CIENCIAS HUMANAS